2011
DOI: 10.1136/gut.2010.222976
|View full text |Cite
|
Sign up to set email alerts
|

Interferon lambdas: the next cytokine storm

Abstract: For two decades the scientific community has sought to understand why some people clear hepatitis C virus (HCV) and others do not. Recently, several large genome-wide association studies have identified single nucleotide polymorphisms (SNPs) linked to interferon lambda 3 (IFNλ3) that are associated with the spontaneous resolution and successful treatment of HCV infection. These observations are generating intense research activity; the hope is that IFNλ3 genetic variants may serve as important predictive bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 53 publications
(106 reference statements)
1
82
0
1
Order By: Relevance
“…GWAS results have indicated that the IL28B rs12979860 (C>T) polymorphism plays an important role in the response for CHC to the treatment and spontaneous clearance of the virus (13,14,17,18,30). While spontaneous viral clearance occurs only in 15-50% of HCV-infected patients, chronic infection develops in the majority (31).…”
Section: Discussionmentioning
confidence: 99%
“…GWAS results have indicated that the IL28B rs12979860 (C>T) polymorphism plays an important role in the response for CHC to the treatment and spontaneous clearance of the virus (13,14,17,18,30). While spontaneous viral clearance occurs only in 15-50% of HCV-infected patients, chronic infection develops in the majority (31).…”
Section: Discussionmentioning
confidence: 99%
“…Formation of ISGF3 complex occurs by the activation of STATs 1 and 2 enabling the fusion of IRF9. The chief entrance for IFN-λ stimulation is considered to be the ISGF3 complex which consecutively causes the activation of STAT 3 and STAT 5 [21].…”
Section: Methodsmentioning
confidence: 99%
“…There are three types of INFs: Type I; consisting primarily of IFN-α and IFN-β (formerly known as leukocyte interferon and ibroblast interferon), type II; consisting of IFN-γ (formerly known as immune interferon) and type III; consisiting of IFN-λ which was identi ied during the recent years and classi ied as a new group. Type I IFNs are produced by many cell types, type II IFN (IFN-γ) is produced by T lymphocytes and NK cells, promote cellular immune responses and type III IFN-λ receptors are highly expressed on hepatocytes [40] (Table 2).…”
Section: Interferonsmentioning
confidence: 99%